Pressure-induced metallization in Mg2Si. (19th May 2017) - Wang, J L; Zhang, S J; Liu, Y; Jin, C Q; Li, N N; Zhang, L J; Liu, Q J; Shen, R; He, Z; Liu, X R
Abstract: Mg2 Si with narrow band gap has attracted increasing interest for its great potential applications. Theoretical calculations have predicted the metallization of Mg2 Si under high pressure. In this work, the electrical resistance and Raman spectrum measurements of semiconducting Mg2 Si were performed to investigate the metallization of Mg2 Si by using diamond anvil cells and strip opposite anvils. A discontinuous change of electrical resistance was found at around 10–13 GPa. Mg2 Si displays a semiconductive-like decreasing trend with increasing temperature before 10 GPa and a metallic-like increasing trend with increasing temperature after 13 GPa. The disappearance of Raman peaks above 9.7 GPa further supported the conclusion of metallization. These results suggest a semiconductor–metal transition at around 9.7 GPa in Mg2 Si, which is close to the theoretical predictive metallization at 6–8 GPa.